Dental bleaching efficacy and impact on demineralization susceptibility of simulated stained-remineralized caries lesions. (February 2019) - Al-Angari, Sarah S.; Lippert, Frank; Platt, Jeffrey A.; Eckert, George J.; González-Cabezas, Carlos; Li, Yiming; Hara, Anderson T.
Abstract: Objectives: To evaluate the efficacy of different bleaching systems on artificially created stained-remineralized caries lesions; and to assess the susceptibility of the bleached lesions to further demineralization. Methods: Human enamel specimens were sectioned, polished, demineralized, and randomly divided into six groups (n = 21) to create stained-remineralized lesions, either non-metallic (non-Met: G1, G2 and G3) or metallic (Met: G4, G5 and G6). G1 and G4 received no bleaching treatment, while G2 and G5 were treated with 15% carbamide peroxide (at-home bleaching protocol; 4 h/d×7), and G3 and G6 with 40% hydrogen peroxide (in-office bleaching protocol; 20min × 3). Susceptibility to further demineralization was tested after bleaching treatment. Lesion mineral loss and depth were measured by transversal microradiography, and color change by spectrophotometry. Outcomes were analyzed using ANOVA models followed by Fisher's PLSD tests (α = 0.05). Results: Metallic-stained lesions were significantly darker (all p < 0.001) and more resistant to bleaching (p < 0.005) than non-Met ones. For both stain types, the at-home bleaching protocol was more effective than the in-office (p < 0.005); however, it also increased the lesion susceptibility to demineralization (p < 0.05) [ΔΔZ mean ± SD ranging from 205 ± 73 to 313 ± 188 (at home) vs. 132 ± 45 to 206 ± 98 (in office); p < 0.05]. After bleaching, non-Met lesions were significantly more susceptible to demineralization (p < 0.05), with the ΔΔZ ranging from 206 ± 98 to 313 ± 188 compared to Met lesions ranging from 132 ± 45 to 205 ± 73. Conclusions: At-home bleaching protocol presented greater bleaching efficacy compared to in-office bleaching protocol. After bleaching, metallic-stained lesions were more resistant to subsequent demineralization compared to non-metallic stained lesions. Clinical significance: Bleaching stained-arrested caries lesions may improve aesthetics but also increase susceptibility to demineralization, depending on the type of stain involved and bleaching system used.